68.5k views
4 votes
I need help on this please​

I need help on this please​-example-1
User Nichol
by
6.2k points

1 Answer

1 vote

Answer:

c) infinite

Explanation:

z - y = 12

-3z + 3y = -36

simplify the first equation to find z in terms of y

z - y = 12

add 12 to both sides of the equation

z - y + y = 12 + y

z = 12 + y

now, substitute z for 12 + y in the second equation.

-3z + 3y = - 36

-3(12 + y) + 3y = -36

-36 -3y + 3y = -36

-36 = - 36

the answer is infinite solutions, because no matter what y and z are, -36 will always equal -36

User Netimen
by
5.8k points